Graphdiyne-based photocatalysts for solar fuel production. Issue 15 (14th July 2022) - Bie, Chuanbiao; Cheng, Bei; Ho, Wingkei; Li, Youji; Macyk, Wojciech; Ghasemi, Jahan B.; Yu, Jiaguo
Abstract : This review summarizes the structure, properties, synthesis, and characterization of graphdiyne and outlines the applications of graphdiyne-based photocatalysts for solar fuel production, including H2 evolution, CO2 reduction, and N2 fixation. Abstract : Graphdiyne is an emerging material widely used in photocatalysis. Its excellent physicochemical properties, such as nonuniform electron distribution, uniform pore distribution, excellent electron mobility, and high chemical stability, make it promising for solar fuel production. Given the rapid development of graphdiyne-based photocatalysts and their application in solar fuel production, a timely review of this field is urgently needed. This paper summarises the structure, properties, synthesis and characterisation of graphdiyne, and the achievements of graphdiyne-based photocatalysts in solar fuel production, including H2 evolution, CO2 reduction and N2 fixation. The challenges and outlook of graphdiyne-based photocatalysts for efficient solar fuel production are presented. This paper is expected to provide new insights into graphdiyne-based photocatalysts for solar fuel production.